A Legal Perspective on Yemen’s Attempted Transition from a Unitary to a Federal System of Government - Williams, Paul; Sommadossi, Tiffany; Mujais, Ayat (Utrecht Journal of International and European Law, 2017)
Yemen’s 2013–2014 National Dialogue Conference paved the way for Yemen to transition from a unitary to federal system of government. This is a common trajectory for States emerging from conflict as federalism offers the hope for greater democratic governance and inclusivity. Nevertheless, there is a danger in assuming that there is an ideal federal model to emulate or that federalism is itself a guaranteed remedy for political dysfunction and authoritarianism. Transitioning to federalism is an arduous, expensive, and technically complicated process. Such transitions can also renew conflict if, prior to the drafting of the federal constitution, key issues related to the design of the new system are not addressed or there is a lack of consensus on how to address those issues. Indeed, this was the case in Yemen. Prior to drafting its new federal constitution, Yemen struggled to reach sufficient political consensus on three key issues: (1) the formation of federal regions; (2) the structure of the new federal system; and (3) how powers were to be distributed in the State, including over natural resources management. This lack of consensus during the National Dialogue Conference resulted in the Constitution Drafting Committee having the responsibility of making highly controversial political decisions about Yemen’s future as a federal State. This article examines how Yemen’s transition to federalism was undermined by the inability to reach sufficient consensus on three key transition issues prior to the drafting of the 2015 federal constitution.